2021
DOI: 10.1002/adem.202101089
|View full text |Cite
|
Sign up to set email alerts
|

Microcellular Ethylene–Vinyl Acetate Copolymer Foam: Life Prediction Under Reciprocating Compression

Abstract: The fatigue law of ethylene–vinyl acetate copolymer (EVA) foam has investigated through its fatigue characteristics of reciprocating compression, to construct its fatigue life prediction model. EVA foam samples are prepared by supercritical fluid foaming method. The MTS‐831 material testing machine is used to perform a reciprocating compression fatigue test with a constant load of 100 000 cycles. The constructed fatigue life prediction model is based on the relationship between the average modulus and the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…EVA foam is generally manufactured by the expansion of the gas dissolved in the matrix melt. The gas can be generated by the separation of a supercritical gas, 7 the vaporization of a volatile liquid, 8 or a gas release by undergoing a chemical reaction of a chemical blowing agent 9,10 . Azodicarbonamide (ADC) is the most employed chemical blowing agent for EVA due to its advantages of high gas yield, nontoxic, and flame self‐extinguishing 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…EVA foam is generally manufactured by the expansion of the gas dissolved in the matrix melt. The gas can be generated by the separation of a supercritical gas, 7 the vaporization of a volatile liquid, 8 or a gas release by undergoing a chemical reaction of a chemical blowing agent 9,10 . Azodicarbonamide (ADC) is the most employed chemical blowing agent for EVA due to its advantages of high gas yield, nontoxic, and flame self‐extinguishing 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Lutfi et al [3] reported the compression and tension behaviors of polyurethane, EVA, Pelite™, and a combination of polyurethane and EVA with a given medium density. Xin [4] and Wen et al [5] explored the mechanical performance and life prediction of EVA foams with five densities of 132, 151, 172, 188, and 209 kg/m 3 under repetitive compressions. Duncan et al [6] highlighted that the mechanical properties of foam materials are closely related to the compressive strain rate.…”
Section: Introductionmentioning
confidence: 99%